BREAKING CHAINS: WOMEN’S IDENTITY CRISIS IN FATIMA BHUTTO AND MEENA KANDASAMY’S NARRATIVES. (International Journal of Food and Nutritional Sciences, 2022)
This paper explores how women’s identity crisis are complexly portrayed in thewritings of two well-known authors, Meena Kandasamy and Fatima Bhutto. It examines thecomplex difficulties faced by female characters in negotiating societal expectations, culturalconstraints, and the quest for selfhood through a close analysis of Fatima Bhutto’s TheRunaways and Meena Kandasamy’s When I Hit You: Or, A Portrait of the Writer as a YoungWife